Design of controlled-release chitosan spheroids prepared by extrusion-spheronization technique using microwave / Zabliza Zakaria - Zakaria, Zabliza (2010)
The interplay effects of matrix formulations with microwave on drug release were investigated using an agglomerate system. Chitosan spheroids were formulated with stearic acid and/or sodium chloride by extrusion-spheronization technique, and chlorpheniramine maleate as water-soluble model drug. The spheroids were treated by microwave at 80 W for 5 to 40 min. The profiles of drug dissolution, drug content, drug-polymer interaction, polymer-polymer interaction, sodium leaching, matrix morphology and integrity were determined. Unlike chitosan matrix prepared by ionotropic gelation method, the retardation of drug release from chitosan spheroids by microwave required a more complex formulation containing both stearic acid and sodium chloride unless a high stearic acid fraction was used. These spheroids demonstrated a high resistance to disintegration during dissolution owing to salt-induced bridging by sodium chloride. In response to microwave, sodium chloride aided stearic acid spread and effected domain interaction via C=O moiety over a matrix with reduced specific surface area thereby reducing drug dissolution. The drug release of spheroids can be retarded by microwave through promoting the layering of hydrophobic stearic acid in a matrix structure sustained by sodium chloride.